Peek-a-boo fairies - Reasoner, Charles (North Mankato, Minn Capstone Picture Window Books, 2014)
In this board book with die-cut pages, fairies dance and play in the sunlight
English stories
1 2 13 15
Keywords: Board books; Fairies -- Juvenile fiction